Pengembangan Pocketbook Sebagai Media Edukasi Dalam Pembentukan First Responder Emergency Response Pada Lingkup Prehospital - Linda Widyarani; Cecilya Kustanti (STIKes MERCUBAKTIJAYA, 2022)
The health cadres play an essential role, as community health educator. The development of pocketbook emergency safety and first aid as a learning media to improve health cadres’s knowledge and skills as first responder emergency response. The purpose of this study is to determine the effect of pocketbook emergency safety and first aid as a learning media in health cadres ability as a first responder emergency response. This study used a quasi-experimental method with one group pre-post test design, with a purposive sampling technique. In this study, the average pretest value of knowledge was 57,50±4,075 and the posttest value of knowledge was 78,27±2,420, with a p-value of 0.000, which means that there is a significant difference between the knowledge before and after the intervention. The average pretest value of practice was 54,80±2,265 and the posttest value of practice was 73,73±1,999, with a p-value of 0.000, which means that there is a significant difference between the practice before and after the intervention.